2018
DOI: 10.5812/ircmj.14469
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Subcuticular and Interrupted Suturing Methods for Skin Closure After Appendectomy: A Randomized Controlled Trial

Abstract: Background: Confirmed evidences on superiority of subcuticular suturing compared to interrupted suturing method, in terms of postoperative complications such as wound infection, size of scar, or abscess formation is few. Objectives: The present study aimed to compare absorbable subcuticular suturing supported with Steri-Strips™ to interrupted nonabsorbable suturing method after appendectomy. Methods: In a randomized controlled trial, seventy patients with the diagnosis of acute appendicitis at Besat hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Other studies showed that cosmetic pleasing and patient satisfaction, which they are signi cantly better in the running horizontal matters and running subcuticular sutures technique than the traditional simple interrupted, are considered essential factors that assess the effect of the suture technique. (7,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that cosmetic pleasing and patient satisfaction, which they are signi cantly better in the running horizontal matters and running subcuticular sutures technique than the traditional simple interrupted, are considered essential factors that assess the effect of the suture technique. (7,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that cosmetic pleasing and patient satisfaction which they signi cantly better in the running horizontal matters and running subcuticular sutures technique than the traditional simple interrupted-are considered as important factors that assess the effect of the suture technique. (6,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…A RCT of 100 patients undergoing open heart surgery compared closure of skin in sternotomy wounds with either transcutaneous or subcuticular suture methods and found infection rates to be increased with subcuticular sutures (2% vs 16%, p = 0.016) and to have no difference in cosmesis [ 27 ]. Another RCT of 70 patients conducted on open appendicectomy wounds found that the width of the scar, and pain at day seven postoperatively were decreased in subcuticular closure, and patient satisfaction was increased in the subcuticular group [ 28 ]. No difference was found in wound complications; however, the study was not powered to detect this.…”
Section: Discussionmentioning
confidence: 99%
“…While the current low-quality evidence demonstrates that transcutaneous sutures show decreased rates of complications, this should be balanced with the burden on the individual patient and the healthcare system to have sutures removed postoperatively. This may account for the decreased patient satisfaction and increased pain at day seven, demonstrated in the study by Javadi et al [ 28 ].…”
Section: Discussionmentioning
confidence: 99%